Critical heat flux of saturated flow boiling for R245fa under hypergravity. (25th January 2023) - Luo, Zufen; Fang, Xiande; Li, Chong; Li, Xiaohuan
Highlights: The gravitational effect on saturated flow boiling CHF for R245fa was measured. Hypergravity enhances flow boiling CHF. When approaching CHF, raising gravity level restrains wall temperature fluctuation. Increasing mass flux diminishes gravitational effect on flow boiling CHF. Abstract: Critical heat flux (CHF) is a very important design parameter for safe operation of heat dissipation applications onboard flight vehicles. Saturated flow boiling CHF experiments, aimed at investigating the influence of hypergravity, were conducted. The working fluid was R245fa refrigerant flowing inside a horizontal copper tube of 2.43 mm inner diameter. A turntable was used to simulate the hypergravity environment. Two mass fluxes (156.7, 236 kg/m 2 s) with different inlet vapor qualities (0.1–0.67) and gravity levels (1 g –2.77 g ) were tested under the inlet pressure of 250.5 kPa. Besides, the limiting heat flux q lim, under which the vapor quality at the tube outlet equals one, was defined for theoretical analysis, and the gravitational effect on boiling curves was provided. The results show that with decrease in inlet vapor quality, CHF increases and outlet vapor quality at the CHF decreases. However, for low mass flux of 156.7 kg/m 2 s and normal gravity, the increase in CHF is weakened with decreasing inlet vapor quality, and the deviation between the CHF and the corresponding limiting heat flux increases. Raising gravity level raises saturated CHF as well as the corresponding outlet vapor quality, and thus narrows the above deviation. For high mass flux (236 kg/m 2 s), the CHFs under different gravity levels (from 1 g to 1.75 g ) are almost the same for the same inlet vapor quality. They increase approximately linearly with decreasing inlet vapor quality, and gradually deviate from the q lim line, corresponding to a decrease of the outlet vapor quality when CHF occurs.